2003
DOI: 10.1074/jbc.m303209200
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potent Peptide Mimetics of Brain-derived Neurotrophic Factor

Abstract: Brain-derived neurotrophic factor (BDNF) has potential for the treatment of human neurodegenerative diseases. However, the general lack of success of neurotrophic factors in clinical trials has led to the suggestion that low molecular weight neurotrophic drugs may be better agents for therapeutic use. Here we describe small, dimeric peptides designed to mimic a pair of solvent-exposed loops important for the binding and activation of the BDNF receptor, trkB. The monomer components that make up the dimers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 44 publications
2
114
0
Order By: Relevance
“…Previous studies have characterized synthetic peptides modeled on loop regions of BDNF, with the goal of using active peptides to derive active non-peptide small molecules that might function as BDNF mimetics (24,53,54). In each of these studies, peptides with neurotrophic activity were found; however, the ability to activate TrkB was either not described (24,53) or not detected (54). Hence whether such peptides can function as ligands that activate TrkB remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have characterized synthetic peptides modeled on loop regions of BDNF, with the goal of using active peptides to derive active non-peptide small molecules that might function as BDNF mimetics (24,53,54). In each of these studies, peptides with neurotrophic activity were found; however, the ability to activate TrkB was either not described (24,53) or not detected (54). Hence whether such peptides can function as ligands that activate TrkB remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described a structurebased design approach that has successfully yielded potent mimics of BDNF (23). Bicyclic dimeric peptides, consisting of a pair of disulfide-constrained mimics of loop 2 of BDNF tethered by either a disulfide or amide link, act as BDNF-like partial agonists in vitro, promoting the survival of chick sensory neurons in culture.…”
Section: Bdnfmentioning
confidence: 99%
“…However, clinical trials using recombinant BDNF have been disappointingly negative (6), presumably because of poor delivery, short half-life, and other limitations. Although efforts have been made to circumvent these problems (7,8), no exogenous agents have been identified that act as potent and selective in vivo agonists of TrkB.…”
mentioning
confidence: 99%